Carrying capacity of mangrove ecotourism area in Pantai Indah Kapuk, North Jakarta, Indonesia - KEVIN EWALDO; MAHAWAN KARUNIASA; NOVERITA DIAN TAKARINA (Society for Indonesian Biodiversity, 2023)
Abstract. Ewaldo K, Karuniasa M, Takarina ND. 2023. Carrying capacity of mangrove ecotourism area in Pantai Indah Kapuk, North Jakarta, Indonesia. Biodiversitas 24: 5809-5820. Mangroves are crucial in providing various ecological and economic benefits to local communities. This study focuses on the economic aspect of mangroves by analyzing their potential as a tourist attraction in the Mangrove Ecotourism, Pantai Indah Kapuk (PIK). The objective of this study is to analyze the carrying capacity of the mangroves as a tourist attraction to ensure sustainable tourism development. The study was conducted in the Mangrove Ecotourism area, Pantai Indah Kapuk, from January to March 2023, utilizing a quantitative approach. The carrying capacity of the mangrove ecosystem was assessed using the Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), and Effective Carrying Capacity (ECC) methods. The calculated values for PCC, RCC, and ECC were 107, 16, and 313 visitors/day, respectively. The analysis revealed that the number of visitors at the PIK Mangrove Ecotourism in 2022 had exceeded the PCC and RCC limits, indicating potential ecological impacts. However, the number of visitors had remained within the ECC limits, suggesting that with proper management, the site could accommodate the current visitor levels sustainably. To achieve long-term sustainability, several initiatives are recommended, such as creating zoning in tourist areas to distribute visitor pressure, increasing the number of field officers to monitor the site, and implementing an online ordering system to manage visitor flow efficiently. The findings of this study contribute to the understanding of the carrying capacity concept in ecotourism and provide valuable insights for the management and conservation of mangrove ecosystems as tourist attractions.